Utilization of Siwalan (Borassus flabellifer L.) Plantation Waste for Kraft Paper Production - Azmi Alvian Gabriel; Yunita Siti Mardhiyyah (Agricultural Faculty, 2019)
Borassus flabellifer L., one of the palm-based commodities in Indonesia which is grows in dry areas especially around the north coast of Java Island. An abundant waste of this plant is a leaf midrib and fruit fiber have an opportunity as a source of lignocellulose for the paper industry. In this study, Kraft paper production was conducted to know the influence of the proportion of Borassus flabellifer L. leaf midrib pulp and fruit fiber pulp, and the concentration of Polyvinyl Acetate (PVAc) adhesives on the sensory and physical quality of kraft paper. The research method used was Randomized Block Design (RBD) with two factors. The Friedman test was used to determine the sensory quality of kraft paper. The physical quality of kraft paper was used ANOVA analysis. The results showed that the treatment of raw material proportion and PVAc adhesive concentration had significant effect on color, surface texture, yield, and tensile resistance, but not significantly different between treatment of gramature and tear resistance. The best treatment of sensory tests was kraft paper with proportion of leaf midrib pulp 50% and fruit fiber pulp 50% and a 7.5% PVAc adhesive concentration. It has a yield value of 72.11%, gramature of 162.80 g/m2, tensile strength of 1.70 %, and tear resistance of 197.6 gf.